Efecto de la terapia con probióticos/ prebióticos sobre la reconstitución del tejido linfoide asociado a la mucosa gastrointestinal durante la infección por el virus de la inmunodeficiencia humana-1 (2017)
HIV infection induces alterations in almost all immune cell populations, mainly in CD4+ T cells, leading to the development of opportunistic infections. The gut-associated lymphoid tissue (GALT) constitutes the most important site for viral replication, because the main target cells, memory T-cells, reside in this tissue. It is currently known that alterations in GALT are critical during the course of the infection, as HIV-1 induces loss of tissue integrity and promotes translocation of microbial products from the intestinal lumen to the systemic circulation, leading to a persistent immune activation state and immune exhaustion. Although antiretroviral treatment decreases viral load and substantially improves the prognosis of the infection, the alterations in GALT remains, having a great impact on the ability to establish effective immune responses. This emphasizes the importance of developing new therapeutic alternatives that may promote structural and functional integrity of this tissue. In this regard, therapy with probiotics/prebiotics has beneficial effects in GALT, mainly in syndromes characterized by intestinal dysbiosis, including the HIV-1 infection. In these patients, the consumption of probiotics/prebiotics decreased microbial products in plasma and CD4+ T cell activation, increased CD4+ T cell frequency, in particular Th17, and improved the intestinal flora. In this review, the most important findings on the potential impact of the probiotics/prebiotics therapy are discussed. © 2017 Rev Med Chile. All right reserved.